Studying the effect of soil factors on some anatomical and morphological properties of Olive (Olea europaea L.) leaves - Ibrahim, Hiyam Jamal; Sedeeq, Ann Ahmed; Kareem, Israa Hawyyiz (Thamar University Journal of Natural & Applied Sciences, 2024)
The current study aimed to evaluate the effect of soil factors on some characteristics of olive leaves. The beginning of the process was collecting plant and soil samples from some home gardens and public street gardens in the City of Kirkuk to conduct tests related to plants and soil. We performed Some tests on the soil to evaluate each type of soil and some properties of olive leaves from different sites. The present study showed differences in physical and chemical properties between the soil collected from home gardens and the soil collected from public street gardens. The electrical conductivity, total dissolved solids, sulfate, and dissolved potassium were higher in the soil collected from Public Street Gardens. In contrast, total nitrogen, phosphorus, calcium, magnesium, and organic matter values were higher in the soil collected from home gardens than in public street gardens. For leaf properties, the results show a significant (P ≤ 0.05) decrease in average leaf area, Leaf dry matter, and Leaf ash in leaves collected from public street gardens compared to olive leaves collected from home gardens. For the structural characteristics of the leaf, the vascular cylinder, cuticle layer, mesophyll, and epidermis were smaller in the leaves of the group from Home Gardens than the leaves of the Public Street Gardens group. In contrast, the leaf edge and thickness were more significant in the leaves from home gardens than in public street gardens.